Teacher agency in synchronous one-to-one Chinese online language teaching : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Linguistics at Massey University, Manawatū, New Zealand - Dai, Chujie (Massey University, 2022)
This study explores the teacher agency of four Chinese language teachers who teach in one-to-one videoconferencing settings. Since these teachers only had limited teaching experience in such a context, four preparatory workshops were designed for the teacher participants before they began teaching. The study seeks to answer three questions: 1) What kinds of competencies did teachers identify as required in their teaching via one-to-one videoconferencing? 2) What kinds of affordances and constraints did teachers perceive in teaching, and how was their agency influenced by these factors? 3) What was the main value of the preparatory workshops from the teachers’ perspective? The study is informed by ecological perspectives and employs a qualitative longitudinal case study approach. The data collected through teaching recordings, stimulated recall interviews, semi-structured interviews and group discussions formed the main data set. The data collected through a teacher questionnaire, written reflection sheets, opinion frames, and text chat on a social media platform formed the supporting data set. The main part of the study, spanning about eight months, comprised three stages. At the first stage, there were four teacher preparatory workshops, each including a lecture and a group discussion. At the second stage, each teacher conducted a series of Chinese learning sessions with a single learner, which were recorded and analysed. At the third stage, semi-structured interviews with individual teachers were conducted. The findings suggest that the teachers identified four important competencies required for online teaching: pedagogical competency, multimedia competency, social-affective competency and the competency of being reflective and reflexive. Different beliefs about teacher roles, perceived social hierarchy, and their relationships with peer teachers and the learners were the factors that enabled or constrained teachers’ actions. The perceived value of the teacher preparatory workshops was in providing opportunities for the teachers to bridge the gap between theories and teaching practice and to explore the pedagogical possibilities. They collectively formed an idealised notion of online teaching as a result of their discussions and this notion influenced their identity and teaching practice. The study concludes with implications for research methodology and a theoretical frame, shedding light on how the factors from the outer world, and teachers’ experience and aspirations could impact the enactment of agency. It is hoped that this study will be valuable for future online language teacher training and research.
Keywords: Chinese language; Study and teaching; Foreign speakers; Web-based instruction; Videoconferencing; Language teachers; Training of; Case studies; 470401 Applied linguistics and educational linguistics; 390499 Specialist studies in education not elsewhere classified